War and democracy: the legacy of conflict in East Africa - Cheeseman, N; Collord, M; Reyntjens, F (Cambridge University Press, 2018)
Abstract The historical literature on statebuilding in Europe has often portrayed a positive relationship between war, state making and long-term democratisation. Similarly, a number of large-n quantitative studies have concluded that war promotes democracy – even in cases of civil war. Against this, a growing area studies literature has argued that violent conflict in developing countries is unlikely to drive either statebuilding or democratisation. However, this literature has rarely sought to systematically set out the mechanisms through which war undermines democracy. Contrasting three ‘high conflict’ cases (Burundi, Rwanda and Uganda) with two ‘low conflict’ cases (Kenya and Tanzania) in East Africa, we trace the way in which domestic conflict has undermined three key elements of the democratisation process: the quality of political institutions, the degree of elite cohesion, and the nature of civil-military relations. Taken together, we suggest that the combined effect of these three mechanisms helps to explain why Kenya and Tanzania have made significantly greater progress towards democratic consolidation than their counterparts and call for more in-depth research on the long-term legacy of conflict on democratisation in the African context.